Glosas de Camões nas Obras Métricas de D. Francisco Manuel de Melo - Ramon, Micaela (2010)
This article examines the theoretical positions of D. Francisco Manuel de Melo relative to literary creation, with particular focus on the concept of imitation, where his thought and practice are occasionally ambiguous. A comparative analysis is made between two of his texts and his Camoen model, as a means of highlighting the varied intertextual relationships existing between the works of each author.